2015
DOI: 10.1177/1933719114565037
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Coregulator CTBP1-AS Is Associated With Polycystic Ovary Syndrome in Chinese Women: A Preliminary Study

Abstract: Polycystic ovary syndrome (PCOS) is currently considered a predominantly hyperandrogenic syndrome. In theory, hyperandrogenism can be caused by high level of testosterone (T) as well as by enhanced androgen receptor (AR) activity. C-Terminal binding protein 1 antisense (CTBP1-AS) was a novel long noncoding RNA (lncRNA) to regulate AR activity. In this study, we found that expression level of CTBP1-AS in peripheral blood leukocytes was significantly higher in women with PCOS than that in controls after adjustme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 57 publications
6
20
1
Order By: Relevance
“…In accordance with this hypothesis, it has been suggested that aberrant cofactor activity due to mutations or altered expression levels may be a contributing factor to PCa progression. In this situation, we speculate whether PCA3 could behave as an AR modulator, by affecting AR activity, AR and their cofactor interactions, or the expression patterns of AR cofactors, as has been proposed for the CTBP1-AS lncRNAs [38]. In support of our proposals, other authors have reported that ncRNAs are able to modulate AR signaling through their cofactors, such as miR-125b [39].…”
Section: Discussionsupporting
confidence: 84%
“…In accordance with this hypothesis, it has been suggested that aberrant cofactor activity due to mutations or altered expression levels may be a contributing factor to PCa progression. In this situation, we speculate whether PCA3 could behave as an AR modulator, by affecting AR activity, AR and their cofactor interactions, or the expression patterns of AR cofactors, as has been proposed for the CTBP1-AS lncRNAs [38]. In support of our proposals, other authors have reported that ncRNAs are able to modulate AR signaling through their cofactors, such as miR-125b [39].…”
Section: Discussionsupporting
confidence: 84%
“…Also a novel lncRNA, namely C-Terminal binding protein 1 antisense(CTBP1-AS), which is known to be a regulator of androgen receptor expression was found to be increased in peripheral blood leukocytes of PCOS women. Its overexpression was correlated with high testosterone and HOMA-IR values (198).…”
Section: Non-coding Rnasas Additional Epigenetic Regulators In Pcosmentioning
confidence: 90%
“…Total RNA was extracted from tissues using an RNeasy Mini kit (Qiagen, Inc., Valencia, CA, USA), as described previously (26). A BioWaveII spectrophotometer (Biochrom, Ltd., Cambridge, UK) was used to evaluate the concentration and purity of the RNA (A260:A280 ratio).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%